PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN TAHU BAXO IBU PUDJI - Maulida, Devi; Budiatmo, Agung (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2018)
The purpose of this study is to determine the effect of product quality and brand image on purchase decision of Tahu Baxo Ibu Pudji Ungaran. Type of research using explanatory research with data collection methods using interviews and data collection tools using questionnaires with a sample of 100 respondents consumers Tahu Baxo Ibu Pudji Ungaran use Purposive Sampling method. The analysis technique used validity test, reliability test, simple linear regression, multiple linear regression, t test, and F test with SPSS 16.0. From result of research indicate that product quality have influence to purchasing decision equal to 43,2%, brand image influence to purchasing decision equal to 62,7%, while simultant product quality and brand image influence to purchasing decision equal to 67,5%. This means that the better the product quality and brand image, the higher the purchase decision of Tahu Baxo Ibu Pudji Ungaran. Brand image variables to purchase decision variables have greater effect than product quality variables. Based on the result of the research, the researcher suggested that Tahu Baxo Ibu Pudji industry to make improvements and developments in packaging design and product durability in order to get better product quality and give good impression to the consumer, and to analyze the level of consumer likeness and loyalty in order to get a better brand image